Does the foreign exchange rate drive stock market returns? Insights from Bangladesh - Mahmud, Aslam; Rahman, Md. Habibur (International Journal of Business, Economics and Management, 2025)
Stock market return and foreign exchange rate are two fundamental indicators of a country’s economic performance. Decision-making in most firms is influenced by fluctuations in exchange rates. It is presumed that there is an impact of exchange rates on stock market returns. This paper examines whether there is any nexus between the BDT-USD exchange rate and the return of the DSEX index in the Dhaka Stock Exchange. The study uses monthly data for the period ranging from March 2013 to April 2023. The methodology of the study includes simple linear regression, Granger causality tests, and VAR impulse response and variance decomposition tests. The findings reveal that both the exchange rate and stock market return series are stationary at the level, and there is no evidence of a causal relationship between them. Regression results show an insignificant negative relationship, and the VAR analysis supports the absence of any meaningful impact. The variance decomposition results further confirm that shocks in one variable account for only a marginal portion of the variance in the other. The study concludes that stock market index return and exchange rate are independent of one another, and there is no causality between them, at least during the observation period. The study findings imply that the stock markets in Bangladesh are safer for foreign investors, as there is a weak relationship between exchange rate return and stock market return.